Biocomplexity of plant-fungal interactions - Southworth, Darlene, 1941- (Ames, Iowa : Wiley-Blackwell, 2012)
Plants interact with a wide variety of organisms in their natural growing environments. Key amongst these relationships is the interplay between plants and diverse fungal species that impact plants in complex symbiotic, parasitic and pathogenic ways. Biocomplexity of Plant-Fungal Interactions explores a broad spectrum of research looking at both positive and negative interactions of these relationships on plants and their ecosystems. Biocomplexity of Plant-Fungal Interactions takes a more holistic view of the plant-fungal interactions than most traditional volumes on the topic. Focusing on the.
Fungal endophytes as a driving force in land plant evolution: evidence from the fossil record / Michael Krings, Thomas N. Taylor, and Nora Dotzler -- Molecular interactions in mycorrhizal development / Jonathan M. Plett and Francis Martin -- Arbuscular mycorrhizas and grassland ecosystems / R. Michael Miller, Gail W.T. Wilson, and Nancy Collins Johnson -- Mycorrhizal networks and seedling establishment in Douglas-fir forests / Suzanne W. Simard -- Biology of mycoheterotrophic and mixotrophic plants / Hugues B. Massicotte [and others] -- Fungi and leaf surfaces / Ryan W. Shepherd and George J. Wagner -- Fungal influence on plant tolerance to stress / Russell J. Rodriguez, Claire J. Woodward, and Regina S. Redman -- Fungi, plants and pollinators: sex, disease, and deception / Tobias J. Policha & Bitty A. Roy -- Dynamic interplay in a multivariate world: case studies in mycorrhizal and endophytic fungal interactions with herbivores / Louis J. Lamit and Catherine A. Gehring -- Biocomplexity in plant fungal interactions / Darlene Southworth.
Includes bibliographical references and index.
Print version record.
Keywords: Plant-fungus relationships; SCIENCE -- Life Sciences -- Mycology; Plant-fungus relationships; Electronic books